2011
DOI: 10.1310/tsr1803-195
|View full text |Cite
|
Sign up to set email alerts
|

The Underutilization of Intrathecal Baclofen in Poststroke Spasticity

Abstract: Stroke is one of the leading causes of adult disability in the United States, with a reported prevalence of 6.4 million people. Spasticity is one of the clinical features of the upper motor neuron syndrome seen after a stroke. The prevalence of spasticity after a stroke ranges from 17% to 42.6%, and an average of two-thirds of people with spasticity have upper and lower extremity involvement. Oral medications and botulinum neurotoxin injections are current treatments for problematic spasticity. However, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…52 Possible reasons for ITB underutilization include surgical risks, excessive weakness, less effect on upper limbs, and limited functional improvement. These concerns are alleviated by recent studies that conclude that the benefits of ITB therapy outweigh the risks.…”
mentioning
confidence: 99%
“…52 Possible reasons for ITB underutilization include surgical risks, excessive weakness, less effect on upper limbs, and limited functional improvement. These concerns are alleviated by recent studies that conclude that the benefits of ITB therapy outweigh the risks.…”
mentioning
confidence: 99%
“…Other studies demonstrated similar findings. 11,12,14,19) It is still unclear why the uninvolved limbs are not affected by ITB, at least clinically. Perhaps ITB has a selective effect on certain spinal cord receptors that also receive supraspinal input modified by the cerebral disease.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, many patients have the potential to benefit from ITB therapy. Patients with some disease process may even be undertreated with regard to this intervention [3,4]. The screening trial may be beneficial for some individuals, however, to suggest that a patient could not benefit from this powerful intervention without first undergoing a screening trial is a bar set too high.…”
Section: Case Scenariomentioning
confidence: 99%